Voluntary Organizations and Community Groups as New Partners in Diabetes Self-management and Education: A Critical Interpretative Synthesis. (October 2015) - Portillo, Mari Carmen; Regaira, Elena; Pumar-Méndez, María J.; Mujika, Agurtzane; Vassilev, Ivaylo; Rogers, Anne; Wensing, Michel; Foss, Christina; Knutsen, Ingrid Ruud; Todorova, Elka; Roukova, Poli; Kennedy, Anne; et al.
Purpose: The purpose of this study is to critically review the literature on the role and work of voluntary organizations and community groups and volunteers in diabetes self-management programs. It seeks to explain how these organizations are located and could be integrated further within a broader system of support. Methods: A critical interpretative synthesis of the literature was undertaken as part of the conceptual development of a European research project. Evidence (2000-November 2014) was searched in databases, with the use of key terms, and limited to the languages of the participating countries. This was supplemented by an additional hand search and snowballing technique. A total of 21 articles were included in the review. Results: Evidence regarding the involvement of voluntary organizations in diabetes self-management programs mainly related to: the nature and remit of their work, responsibilities, and attributes; key strategies of programs accounting for success; motivations/barriers for engaging in volunteering participation; relationships between volunteers and users; and connections/tensions with formal services. Conclusions: This review has uncovered a range of facets of voluntary organizations and community groups relevant for supporting diabetes self-management such as the context within which they act and the nature of relationships developed with community and health services. The principles of "assistance, support, sharing, and link" seem essential for this voluntary initiative in self-management to establish effective reciprocal collaboration with health professionals.